Defining aspects concerning the rural household and the sustainable socio-economic development in Romania - Lorena Florentina Chiţea; Ion Dona (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
Rural development has as main subject the rural space as a system in which the main components (natural resources, people) interfere and have a specific (economic, social, cultural, political, institutional) behaviour. The rural household is the main actor in the rural space, owner of the main (natural, human, economic, cultural) resources, which it uses at its own discretion and whose behavior is very important for the society where it belongs. The need for this study stems from the necessity of the Romanian rural household to get adapted to the new Romanian and European socio-economic development realities. Even though the modernization paradigm has been replaced by the rural development paradigm, the Romanian rural communities and agriculture must continue their modernization process, which had a sinuous evolution rather than a continuous constant evolution as in the case of the developed countries from Europe, taking into consideration the new orientations of the current rural development.
Keywords: R20; Q01; O2; 330; rural area; rural household; sustainable development